PENGEMBANGAN UMKM PEYEK DENGAN BERFOKUS PADA DIGITAL MARKETING PADA DESA TELANG SARI, KECAMATAN TANJUNG LAGO - Oktavia, Wayan Suci; Heriyanto Heriyanto; Andrian Noviardy; Dina Mellita; Jemakmun Jemakmun (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program aims to enhance the digital marketing capacity of Ibu Surita's "Peyek" MSME in Telang Sari Village, Tanjung Lago District. The background is the limited use of social media and branding in this micro-business. The methods used were observation, interviews, socialization, practical training, and mentoring. The results show an improvement in the business owner's digital literacy, evidenced by the ability to manage a WhatsApp Business account, upload promotional content, and the implementation of new packaging label designs that strengthen brand identity. This intervention provided benefits such as expanding potential market reach, improving product image, and motivating the business owner to continue developing digital marketing independently.